Pengembangan Bahan Pembelajaran E-Modul Dasar Perakitan Komputer dalam Mata Pelajaran Informatika - Kholiduni’am, Yasin; Supandi, S; Wijonarko, W (SAFE-Network, 2023)
This research is motivated by efforts to develop learning materials to make them more interesting, easy to understand, and efficient, especially in learning Informatics which is known based on observations at SMK N 1 Blora. Seeing these conditions, it is necessary to strive for the use of learning media to foster student interest and make it easier for students to understand basic computer assembly learning. The media used is E-Learning Module. The purpose of this study is to describe the results of the application of E-Modules in basic learning of computer assembly in class X DKV3 SMK N 1 Blora. The approach used in this research is a qualitative descriptive approach. Sources of data obtained from learning outcomes using E-Modules as teaching materials for students of class X DKV3 SMK N 1 Blora for the academic year 2021/2022. Collecting data in the form of test and non-test results, with the aim of knowing student learning outcomes using E-Module learning media. The technique of presenting the results of data analysis is carried out qualitatively, namely the results of the research are presented by describing the state of the class when carrying out research and the authors analyze and describe the application of E-Modules as a learning medium for students of class X DKV3 SMK N 1 Blora in the 2021/2022 school year. The use of pictures, animations, and videos in the learning process can stimulate students to be more interested and creative so that it helps students more easily understand the learning material provided. The application data from the learning E-Module media obtained an average value of 85.4, the highest score was 93.5 and the lowest score was 72.5.